SIMULASI KETERSEDIAAN AIR BULANAN DENGAN BASIS DATA SPASIAL FAKTOR-FAKTOR SUMBER DAYA AIR: KASUS SUB-DAS HULU CITARUM - Djuwansah, Muhamad Rahman (Teknologi Indonesia, 2010)
Spatial Monthly Water resources Database of Bandung Basin has been developed to fulfi ll the necessity of more detailed quantitative water resources information. Database development was based on soil water balance using Curve Number (CN) method, distribution of soil permeability tension (pF) and hydraulic conductivity (k) of existing rocks. Input data were monthly isohyet, land use, soils and geologic maps that were processed in GIS software. Isohyet was derived derived from rainfall data and DEM, whereas land use map was derived from satellite LANDSAT/ASTER image. The objective of this paper is to represent simple and appropriate procedure for 1:5000 map scale resolution, in simulating monthly water availability. The outputs of the calculation could be presented as monthly thematic maps of water resources component such as surface water, evapotranspiration, infi ltration and percolation, as well as graphics of tabular data for over all study region or selected area. The estimation results from the data of 2001 and 2004 show the increase of surface run-off and decrease of groundwater availability due to land-use change and rainfall decrease. This database can be use to forecast the future water resources availability caused by land use changes as well as by climatic changes.